2021
DOI: 10.1088/1361-648x/ac1823
|View full text |Cite
|
Sign up to set email alerts
|

A study on the room-temperature magnetoplastic effect of silicon and its mechanism

Abstract: Exposure to a magnetic field at room temperature was found able to promote the dislocation motion and distortion relaxation in silicon. The Kernel average misorientation maps of the silicon samples obtained by electron backscatter diffraction (EBSD) showed that a magnetic field ∼1 T can cause dislocation movement of hundreds of nanometers. And the EBSD image quality maps indicated that the magnetic field can cause the relaxation of the lattice distortion. The Δg mechanism of the magnetically stimulated changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, it should be noted that, according to the ∆g mechanism, transition from the singlet state to the triplet state is also promoted, and it should also be taken into consideration [60]. A more detailed theoretical analysis was employed to obtain the density matrix of four spin stats under the external magnetic field [69]. By calculation, the magnetoplastic effect was no longer attributed to the extended average life of the excited state of the reaction system caused by the external magnetic field, but to the change in the probability distribution of the life of the excited state.…”
Section: Mechanism For Microstructure Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that, according to the ∆g mechanism, transition from the singlet state to the triplet state is also promoted, and it should also be taken into consideration [60]. A more detailed theoretical analysis was employed to obtain the density matrix of four spin stats under the external magnetic field [69]. By calculation, the magnetoplastic effect was no longer attributed to the extended average life of the excited state of the reaction system caused by the external magnetic field, but to the change in the probability distribution of the life of the excited state.…”
Section: Mechanism For Microstructure Modificationsmentioning
confidence: 99%
“…A more detailed analysis starts from the spin configuration representation [69]. Omitting the initial derivation, the density matrix ˆ( ) t  of the spin states (S, T 0 , T + , T -) can be written in Eq.…”
Section: Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…When sorting out the magnetic field assisted treatment and independent treatment, it was found that the essence of the alloy properties changes is that magnetic field affects the movement of dislocation, mainly reflected in: (1) Dislocation de-pinning effect: magnetic field weakens the bonding force between atoms, and enhances the atomic mobility. It causes dislocation loosening at the pinning place [47][48][49]. (2) Dislocation core expansion: the expansion of dislocation core is caused by magnetic field in the process of dislocation de-pinning, which reduces the pinning resistance of dislocation movement and improves the effective stress driving dislocation movement [48].…”
Section: Magnetic Field Promotes Dislocation Motionmentioning
confidence: 99%